Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/phar.1738
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Incidence of Acute Kidney Injury in Critically Ill Patients Receiving Vancomycin with Concomitant Piperacillin‐Tazobactam or Cefepime: A Retrospective Cohort Study

Abstract: After adjusting for propensity to receive each of the treatment choices, no significant difference was found in the incidence of AKI development or other outcomes between the groups. The previously described finding that concomitant vancomycin and piperacillin-tazobactam increases AKI in non-critically ill patients may not be generalizable to the critically ill population. Prospective evaluation of this hypothesis is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 49 publications
(185 reference statements)
4
102
1
Order By: Relevance
“…To our knowledge, this is the largest study to date to examine the difference in AKI incidence among patients treated with VAN and FEP or PTZ. We found the AKI rate in patients treated with VAN-TZP to be 21.4%, whereas the range of the incidence found in the current literature is 9.5 to 34.8% (8)(9)(10)(11)(12)(13)(14)(15)(16). The AKI incidence in the VAN-FEP group was similar to previous reports of 12.5% (9,10).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…To our knowledge, this is the largest study to date to examine the difference in AKI incidence among patients treated with VAN and FEP or PTZ. We found the AKI rate in patients treated with VAN-TZP to be 21.4%, whereas the range of the incidence found in the current literature is 9.5 to 34.8% (8)(9)(10)(11)(12)(13)(14)(15)(16). The AKI incidence in the VAN-FEP group was similar to previous reports of 12.5% (9,10).…”
Section: Discussionsupporting
confidence: 54%
“…In addition, aside from the study of Gomes et al (10), confounding was not adequately addressed in the studies, further limiting their application. Our study attempted to rectify these issues by including a larger number of patients (4,193 in the present study versus 485 in the previous studies combined) (9)(10)(11) and utilizing a propensity score matching algorithm to control for confounders. The difference in AKI incidence was maintained after controlling for confounders, suggesting that the use of TZP is associated with increasing rates of AKI compared to those achieved with the use of FEP when the drugs are combined with VAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous risk factors exist for vancomycin-associated nephrotoxicity, including vancomycin trough concentrations3 ≥15 mcg/mL, concomitant exposure to other nephrotoxins, such as aminoglycosides4 and piperacillin/tazobactam5,6,7,8,9,10,11,12,13, duration of exposure,12,14-16, and total daily dose 15,17. Due diligence is necessary when vancomycin is used in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Two adult studies showed that compared to vancomycin monotherapy, when vancomycin is used in conjunction with piperacillin/tazobactam the odds of hospitalized non-critically ill adult patients developing AKI increased by 2.48 to 5 times [54, 55], though indication bias is difficult to control for. A more recent study showed no increased risk of AKI using this drug combination in critically ill adults [56], so this risk may differ by population studied. Finally, there is even some evidence suggesting more substantial nephrotoxicity associated with piperacillin/tazobactam independent of vancomycin [2].…”
Section: What Drugs Are the Biggest Offenders?mentioning
confidence: 99%